Biological properties of cucumber (Cucumis sativus L.) extracts - How, Fiona Ni Foong; Mohammad, Aqeelah; Arief Ichwan, Solachuddin Jauhari (2014)
Peel and pulp of Cucumis sativus L. fruit were extracted from aqueous (water) and phosphate buffered solution at incubated temperature of 37 deg celsius similar to normal human physiological temperature to investigate the potential of these extracts as antibacterial agents and cytotoxic agents using antibacterial susceptibility assay against six pathogenic bacteria of gram positive and negative and cytotoxic assay against Human non-small cell lung carcinoma cell line (H1299) and Human breast adenocarcinoma cell line (MCF-7). The phytochemical contents of all the extracts were determined to correlate with their biological properties.